Epigenotype and phenotype correlations in patients with Beckwith-Wiedemann syndrome - Bilgin, Burçak; Kabaçam, Serkan; Taşkıran, Ekim; Şimşek-Kiper, Pelin Özlem; Alanay, Yasemin; Boduroğlu, Koray; Utine, Gülen Eda (The Turkish Journal of Pediatrics, 2018)
Beckwith-Wiedemann Syndrome (BWS) is one of the most common overgrowth syndromes. Cancer predisposition is an important feature of this clinically heterogeneous syndrome. Patients may have fetal and early childhood overgrowth, hemihyperplasia, macroglossia, facial dysmorphic features, abdominal wall defects, visceromegaly, and anomalies of the heart and the kidneys. Various previous investigations showed that heterogeneous molecular etiology may contribute to clinical variability and that epigenotype-phenotype correlations exist in BWS. This study was performed to detect the molecular etiology in 28 patients with BWS, to search for epigenotype-phenotype correlations and to provide appropriate individualized multidisciplinary approach. Four different molecular etiology groups were determined based on testing for copy number analysis and methylation status at 11p15. Sequencing for CDKN1C mutations were also performed. Groups were compared for various clinical findings. Differences between groups were not statistically significant owing to the small number of patients in individual groups. Statistical studies for epigenotype-phenotype correlations showed significance for only anterior ear lobe creases, visceromegaly and embryonal tumors. Additionally, one interesting patient had a mesenchymal tumor. Anticipating follow-up is clinically important in BWS.
Keywords: Beckwith-Wiedemann syndrome (BWS); Wilms tumor; epigenotype and phenotype correlation; imprinting; uniparental disomy